INFLUENCER CONTRIBUTIONS; DOES IT AFFECT MARKETING CONTENT FOR MSMEs’ CUSTOMER ENGAGEMENT? - Erwin Erwin; Cipta Canggih Perdana; Yuyun Karystin Meilisa Suade (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The primary activity for businesses on social media is the creation of content, including both persuasive and informative content. Influencers are also thought to exist because they aid in the distribution of content related to commercial actors' products. This study examines the role of content marketing and influencers in boosting MSMEs' social media customer engagement. The respondents in this study were 234 MSME actors who were users of social media. The data was collected using a questionnaire with a Likert Scale (5 Scale). The acquired data was analyzed using the Partial Least Square Structural Equation Model (PLS-SEM) and then processed using WarpPLS Version 8.0. Based on the data analysis findings, it was discovered that the social media influencers and both informative and persuasive content directly had a positive and significant influence on MSME customer engagement, but that influencers were unable to adequately contribute to the influence of marketing content on customer engagement. In marketing materials created by the MSME actors, the influencers may be used separately. The influencers had their own goals in order to increase client interaction for MSMEs on social media.